Morphological and neurophysiological impairment of the nerve in type II macrodactyly - Yang, Xi (PLoS One, 2018)
BACKGROUND: Macrodactyly is a congenital malformation characterized by aggressive overgrowth of multiple tissues, including subcutaneous fat, nerves, and bones in digits or limbs. In type II macrodactyly, the peripheral nerve is enlarged; however, the morphological and functional characteristics of the affected peripheral nerves have rarely been evaluated. METHODS: In this research, six macrodactyly patients and three polydactyly patients (control) were studied. Pre-operative sensory nerve action potential and intra-operative nerve action potential tests were performed. The microstructure and ultrastructure of the enlarged nerves were observed and neurofilament (NF) expression was evaluated using immunofluorescent staining. RESULTS: Axon impairment of the digital nerves originating from the median nerve (MN) was observed. A compensatory reinnervation from the ulnar nerve (UN) was found in two of the six patients, and significant morphological changes were observed in the enlarged nerve. The myelinated nerve fibers decreased, the lamellar structure of the myelin sheath changed, and the density of the NFs of the unmyelinated fibers decreased. There was aberrant distribution of NFs in the macrodactylous nerve tissues. In patients with compensatory UN reinnervation, the number of myelinated and unmyelinated fibers increased to normal levels; however, the diameter of the myelinated fibers apparently decreased. CONCLUSIONS: The morphology and function of the macrodactylous enlarged nerve was impaired in type II macrodactyly patients; however, the unaffected UN partially compensated for the lost function of the affected MN under specific situations. Electrophysiological tests should be performed to determine the function of the affected nerve and surgical treatment for type II macrodactyly could be refined.